Effects of shrimp chitosan based edible coating on the shelf life of selected vegetables in context of attaining SDGs - Munir Ibn Mahin; Md. Harun-Ar Rashid; Abdul Rabbi Mredul (Applied Food Research)
Vegetable spoilage and post-harvest losses are worldwide issues that diminish quality, nutritional content and marketability, hence exacerbating food waste and threatening food security, particularly in agriculturally dependent countries like Bangladesh. Polysaccharide coatings, particularly chitosan, have gained popularity as biopolymer-based coatings for prolonging the postharvest shelf life of fruits and vegetables, owing to their biodegradable and non-toxic properties. This study aimed to assess the characteristics of chitosan obtained from shrimp (Penaeus monodon) shells and uses it as coatings to prolonging the shelf life of tropical vegetables. The extraction and characterization of chitosan as well as its effect on the shelf life of vegetables were evaluated. The study yielded approximately 20.85 ± 0.01 % of chitosan from the shrimp shell. The moisture content, WBC and FBC were 8.68 ± 0.01 %, 564.67 ± 4.73 % and 518.00 ± 5.57 % respectively. The intrinsic viscosity of chitosan was 20.74 dL/g with a molecular weight of 114.01 kilodaltons (kDa). The solubility of the chitosan was 99.90 % ± 0.10 % with a DD of 95.88 ± 0.70 %. The FTIR spectra of the chitosan sample were measured with specific peaks at 3410.96 cm-1, 3294.30 cm-1, 2989.75 cm-1, 1655.67 cm-1, 1553.79 cm-1, 1403.18 cm-1, 1051.56 cm-1, 829.64 cm-1. Concentration of chitosan 0.5 % (CS-0.5) resulted in the most significant at shelf-life extension with carrots, green tomatoes, tomatoes, cucumbers and beans showing increases of 12, 21, 21, 21, and 14 days, respectively, signifying the practical potential of chitosan-based edible coatings in vegetables preservation. Chitosan derived from Penaeus monodon has favorable characteristics for reducing vegetable's postharvest loss. Chitosan-based edible coatings improve food preservation and support sustainable practices, aiding in attaining 2, 3, 12, and 13 UN Sustainable Development Goals (SDGs).